Quality of life of elderly people living with HIV/AIDS in outpatient follow-up - Juliano de Souza Caliari; Lilian Andreia Fleck Reinato; Daiana Patrícia Marchetti Pio; Letícia Pimenta Lopes; Renata Karina Reis; Elucir Gir
ABSTRACT Objective: To analyze factors related to the quality of life of elderly people living with HIV/AIDS. Method: A cross-sectional study was carried out with people aged 50 years or more in a specialized outpatient clinic. The data collection was by means of an interview. For the analysis of data and characterization of the sample, descriptive statistics and comparison tests were used. The project met the ethical requirements. Results: Participants were 81 users aged 50 to 75 years, mean age was 57.8 (± 6.1) years, 71.6% of whom were men. There was a statistically significant relationship with the quality of life, the following variables: gender, children, occupation, religion, diagnosis time, HIV exposure, adverse effects, treatment interruption, viral load counts, hospitalization, dependence for daily activities and use of drugs. Conclusion: The results suggest that the quality of life deficit is related not only to physical changes, but to the anguish and stigma related to HIV/AIDS.